IMPLEMENTASI PEMENUHAN HAK PENYANDANG DISABILITAS DALAM PENGGUNAAN SARANA DAN PRASARANA TRANSPORTASI BERDASARKAN PERATURAN DAERAH PROVINSI RIAU NOMOR 18 TAHUN 2013 TENTANG PERLINDUNGAN DAN PEMBERDAYAAN PENYANDANG DISABILITAS DI KOTA PEKANBARU - Simanjuntak, Eben Haizer; Firdaus, Emilda; Rauf, Muhammad A. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
In order to realize the availability of accessibility of transportation facilities and infrastructurefor people with disabilities, a full understanding of policy makers is still needed both in the center and inthe Pekanbaru City area. There are still many public facilities and infrastructure that need attention.People with disabilities have the same right to mobility in order to fulfill their daily activities. Providingaccessibility for people with disabilities is an obligation, not a compulsion. Article 17 paragraph (1) of theRiau Provincial Regulation Number 18 of 2013 concerning the Protection and Empowerment of Peoplewith Disabilities states that every person with disabilities has the right to the provision of accessibility inthe utilization and use of public facilities and infrastructure, the environment and transportation facilitiesand infrastructure.This type of research is sociological legal research, because it is based on field research,namely by collecting data through interviews, questionnaires, and literature studies, reviews related to theproblems to be studied assisted by primary, secondary and tertiary data. This research was conducted atthe Pekanbaru City Transportation Service, the Pekanbaru City Social Service, while the population andsample were all parties related to the problem being studied. This research uses qualitative data analysisand produces descriptive data.From this study, it can be concluded that the implementation of the fulfillment of the rights ofpersons with disabilities in the use of transportation facilities and infrastructure has not been runningoptimally. Inhibiting factors in the implementation of the fulfillment of the rights of persons with disabilitiesin the use of transportation facilities and infrastructure are due to inadequate budget factors, unpublishedsupporting regulations, weak human resources, limited facilities and infrastructure, and lack ofsocialization, education and supervision from the Pekanbaru City Social Service and the Pekanbaru CityTransportation Service. Efforts made by the Pekanbaru City Government through the Pekanbaru CityTransportation Service in implementing the fulfillment of the rights of persons with disabilities are toincrease the procurement and renovation of special road signs/markings for persons with disabilities,provide bus stops and terminals that are more friendly to persons with disabilities.Keywords: Disability, Implementation of Regional Regulations, Transportation Facilities andInfrastructure